“Effect of Palatal Metal Collar’s Height on Fracture Resistance of Single Metal-Ceramic Crowns” - Nour Aburaisi; Haitham Elbishari (International Journal of Dentistry, 2022)
Objectives. The purpose of this study is to evaluate the effect of the palatal metal collar height on the fracture resistance of metal-ceramic crowns. Materials and Methods. A maxillary premolar typodont tooth was prepared and scanned to fabricate 48 metal analogs. The analogs were then scanned to fabricate metal copings divided into 4 groups according to palatal metal collar height as follows; (C0): 0 mm, (C1): 1.0 mm, (C2): 1.5 mm, and (C3): 2.0 mm. After a standard application of pressed ceramic, each crown was cemented onto its corresponding metal tooth analog. The crown-analog assembly was subjected to a sequence of thermal stressing for 5,000 cycles. A universal testing machine applied controlled loads to the crowns until fracture. Examination under a stereomicroscope determined the failure mode. A scanning electron microscope (SEM) was used to examine fracture. Load to failure data was analyzed using ANOVA followed by Tukey HSD (P≤0.05). Results. ANOVA statistics revealed that groups with a palatal metal collar presented significantly higher failure loads when compared to the collarless group (P<0.0001). Difference in failure loads between 1.5-mm and 2.0-mm palatal metal collar height were not statistically significant (P=0.935). There were no significant differences detected among the groups in terms of failure mode. Conclusions. The height of the palatal metal collar has an effect on the fracture resistance of the metal-ceramic crowns. Clinical Relevance. The incorporation of a palatal collar with a predetermined height is essential to reduce the mechanical failure of metal-ceramic crowns.